Sifat Machiavillan, Komitmen Profesional Mahasiswa Terhadap Intensi Kecurangan Dengan Jenis Kelamin Sebagai Variabel Mod-erasi - Bill Enus Mauboy; David Adechandra Ashedica Pesudo (AFRE (Accounting and Financial Review), 2019)
Cheating is usually the most common we encounter in the business world, but we do not rule out the possibility of cheating we can also find in the world of education. This study aims to analyze the effect of machiavellian traits, professional commitment, and gender as moderating variables on academic cheating intentions. This research was conducted at the Satya Wacana Christian University's economics and business faculty with purposive sampling techniques. The analysis technique used is multiple regression analysis and moderation analysis techniques. The results of this study indicate that machiavellian traits have a positive effect on academic cheating intentions, and professional commitment does not affect the intention of academic fraud. Besides, gender also weakens the machiavellian relationship and professional commitment to academic cheating intentions. DOI: https://doi.org/10.26905/afr.v2i2.3727